Manajemen Komitmen Dalam Profesi Mengajar - Fauziyah, Ade Eva; s, Suhada (The International Journal of Pegon : Islam Nusantara civilization, 2024)
Organizations must pay attention to human resource factors in increasing commitment to the organization to fully optimize their competencies. Organizational commitment is a high sacrifice made by employees to the organization and certain beliefs in accepting organizational values. This research aims to present a number of study results regarding strategies for increasing employee performance and loyalty through organizational commitment. Commitment is an attitude that reflects the extent to which an individual knows and is attached to his organization. Some commitments in the teaching profession include care, responsibility and loyalty. Elements of organizational commitment include a strong desire to remain a member of the organization, a willingness to really strive for the interests of the organization and a strong belief in and acceptance of the organization's values ​​and goals. Next is the approach to commitment, namely the ability and willingness to align personal behavior with the needs, priorities and goals of the organization. This includes ways of developing goals or meeting organizational needs that essentially prioritize the organization's mission over personal interests. Organisasi harus memperhatikan faktor sumber daya manusia dalam meningkatkan komitmen terhadap organisasi untuk mengoptimalkan sepenuhnya kompetensi yang dimiliki. Komitmen organisasi merupakan pengorbanan yang tinggi yang dilakukan oleh karyawan kepada organisasi dan keyakinan tertentu dalam penerimaan nilai- nilai organisasi. Penelitian ini bertujuan untuk memaparkan sejumlah hasil studi tentang strategi peningkatan kinerja dan loyalitas karyawan melalui komitmen organisasi. Komitmen merupakan sikap yang mencerminkan sejauh mana seorang individu mengenal dan terikat pada organisasinya. Beberapa komitmen dalam profesi mengajar meliputi kepedulian, tanggungjawab dan loyalitas. Unsur-unsur komitmen organisasi diantaranya adalah keinginan yang kuat untuk tetap menjadi anggota dalam organisasinya, kerelaan untuk sungguh-sungguh berusaha demi kepentingan organisasi dan keyakinan yang kuat dan menerima nilai dan tujuan organisasi. Selanjutnya adalah pendekatan terhadap komitmen yaitu kemampuan dan kemauan untuk menyelaraskan perilaku pribadi dengan kebutuhan, prioritas dan tujuan organisasi. Hal ini mencakup cara-cara mengembangkan tujuan atau memenuhi kebutuhan organisasi yang intinya mendahulukan misi organisasi dari pada kepentingan pribadi.